(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2016)
Background: Rhinosporidiosis has been known for over a hundred years since its first description in Argentina. It is a chronic granulomatous,non contagious infective condition characterized by a production of nasal polyps and other manifestation of nasal hyperplasia, with frequent recurrence after surgery. The objective of this present study was Impact of Socio-economic condition of patients on Rhinosporidiosis. Methods: 34 number of patients were included in this study with symptomatic Rhinosporidiosis.The main outcome of study were age, sex, socioeconomic status, Occupation, bathing habit and living area of patients. Results: The study showed that 61.76 percent of patients were in the age group of 6-20 years. The mean age of 20.62 (SD±13.87) years. Most of the Rhinospridiosis patiets were from lower economic class 24(70.59%) followed by middle class 9(26.47%) and 1(2.94%) patients were upper class of socioeconomic status.Student was the most common occupation of Rhinosporidiosis 17(50%) followed by farmer 7(20.59%). Most of the Rhinosporidiosis patients 31(91.18%) were taking bath in pond where cattle also take bath. Conclusion: Rhinosporidiosis are very common in male and frequent age incidence are 6-20 years. Most of the Rhinospridiosis patient were from lower economic class and most of the Rhinosporidiosis patient were taking bath in pond where cattle also take bath. Chatt Shi Hosp Med Coll J; Vol.15 (1); Jan 2016; Page 12-16